A System for Decoding and Coloring Arabic Text for Language Learners - Al-Khalifa, Hend S. (IEEE access, 2019)
Language learners face difficulties while reading and comprehending Arabic text, this is because of the interwoven nature of Arabic script. In this paper, we present (Arcode) an automatic web-based system, which simplifies instruction on Arabic word decoding and comprehension through utilizing color-coding on Arabic text. The system is designed to help Arabic language learners to analyze and identify attached affixes (prefixes & suffixes), particle and silent letters of the selected text, and sentences based on the sentence morphological structure. This is done by encoding and presenting color conversion per word and character, using a certain color code. The proposed system is a combination of color-coding technique, transliteration, and text-to-speech technologies that creates an educational tool for learning the Arabic language. It also provides web services for developers who want to integrate the system into their own applications.